Mutagenic Effect of Temperature-Sensitive Mutants of Gene 42 (dCMP Hydroxymethylase) of Bacteriophage T4 - Chiu, Che-Shen (1973)
Certain temperature-sensitive mutants of gene 42 of bacteriophage T4 increase the reversion rates of some rII mutants in the same genome by about 4 to 10 times. This effect was usually found at 34 C, an intermediate permissive temperature, but not at 28 C.